The appearance of product innovation in the life of a Hungarian SMEs in the global market of sporting goods - implications from a research - Kornélia V. MÓRIK; Éva BÁCSNÉ BÁBA; Anetta MÜLLER; Gergely Gábor RÁTHONYI; Anikó MOLNÁR (Editura Universităţii din Oradea, 2019)
For a Hungarian SME to keep its already acquired position in the global market of sporting goods is a continuous and complex task in which innovation plays a key factor. The purpose of our research is to certify the necessity and the appearance of innovation in the life of a product in the sports business - this case concerning the production of NAJADE fins. This work helps to identify the trends of the consumer attitudes, which is an essential information in product development. The result of the survey (N=200) regarding the needs of consumers shows that however product design plays a secondary role to the quality, durability and the results reached with the product, it is still an influencing factor in product selection. Since sports equipment are used to achieve better results with, the technical improvement of the product is an important aspect of product innovation. Furthermore, the biological acceleration of the generations and the specific needs of the different kind of underwater sports should be taken into consideration when manufacturing these products. Moreover, to reach lower income, developing countries with our products, cheaper, cost-effective technological proceedings could mean a solution.